Psychological and physiological stress in non-competitive and competitive esports settings: A systematic review. (November 2020) - Leis, Oliver; Lautenbach, Franziska
Abstract: Objectives: Competition is related to psychophysiological stress responses and is a key aspect of esports. Yet, while competition may indeed have an impact on performance, little is known about competition-related psychophysical stress responses in esports. Accordingly, this review aims to investigate whether playing esports in competitive (and non-competitive) settings is related to psychological and/or physiological stress. Design: A systematic literature review was performed. Study inclusion criteria included: assessment of psychological and/or physiological stress in esports, study of healthy individuals over 12 years of age, and published in peer-reviewed journals in English or German. Method: The literature search comprised EBSCOhost, PubMed, and Web of Science up until August 2019. An additional search was performed on Science Direct, Google Scholar, and Sponet. Results: Seventeen studies met inclusion criteria. In publications investigating the non-competitive setting, it can be assumed that merely playing esports games is unrelated to psychophysiological stress reactions. While three out of five studies on stress in competitive settings demonstrated no hormonal reaction, one study reported an increase in anxiety levels in winners as well as an increase cortisol levels from baseline to postgame conditions, and two studies found an activation of the sympathetic nervous system. Overall, the studies revealed theoretical and methodological limitations, which are discussed in the present review. Conclusions: Although the existing literature contributes to an initial understanding of psychophysiological stress in esports, further in-depth studies of stress responses in actual competition are needed. Highlights: This review provides a starting point for future research on psychological and/or physiological stress in esports. Playing esports non-competitively seems not be related to psychophysiological changes. Three out of five studies on stress in competitive settings demonstrated no hormonal reaction. An activation of the sympathetic nervous system and changes in psychological stress was shown in two competitive studies. Studies revealed theoretical and methodological limitations, which are discussed in the present review.